Real-Time Implementation of Integrated Optical Plus Filtered OFDM 5G Network Parameters for LTE and DVB-T2 Telecommunication Systems - Ahmed-Ade, Fatai; Akpan, Vincent Andrew; Ogolo, Emmanuel Omonigho (PT. Teknologi Futuristik Indonesia, 2026)
Orthogonal Frequency Division Multiplexing (OFDM) technology to deliver mobile broadband and digital television services. This paper presents the real-time implementation of Optical plus Filtered OFDM (O+F OFDM) algorithms for Long Term Evolution (LTE) mobile networks and Digital Video Broadcasting – Second Generation Terrestrial (DVB-T2) systems, with particular focus on deployments in emerging markets. The paper analyzes physical-layer configurations specified in 3GPP TS 36.211 and ETSI EN 302 755, including subcarrier spacing, Fast Fourier Transform (FFT) sizes, cyclic prefix options, modulation schemes, and Multiple-Input Multiple-Output (MIMO) configurations. Field measurements from Nigerian LTE deployments reveal that while theoretical peak rates approach 300 Mbps with 4×4 MIMO on 20 MHz carriers, achieved throughput typically ranges from 15-35 Mbps due to backhaul constraints, interference, and suboptimal network configuration. For DVB-T2, we document parameters enabling 30-50% greater spectral efficiency than first-generation standards through enhanced forward error correction, larger FFT options (up to 32k subcarriers), and rotated constellations. The O+F OFDM implementation demonstrates superior performance characteristics: reduced out-of-band emissions (>45 dB suppression), improved spectral confinement within regulatory masks, and enhanced multipath resilience through optical filtering stages. System-level considerations including adaptive modulation and coding, Quality-of-Service (QoS) bearer management, Self-Organizing Network (SON) algorithms, and carrier aggregation are examined. We strongly recommend Field-Programmable Gate Array (FPGA)-based real-time implementation of O+F OFDM for both MTN's LTE and GOtv's DVB-T2 systems to achieve deterministic signal processing latency below 5 microseconds, support adaptive parameter reconfiguration without hardware modifications, and enable power-efficient operation critical for Nigerian deployment scenarios with unreliable electrical infrastructure.